Work Life Balance And Job Satisfaction Of Lecturer In Faculty Of Economics And Business Unjani - Dian Lestari; Rahardianto (Publisher Cv. Inara, 2021)
This study aims to determine the effect of work life balance on job satisfaction of lectures at Economy and Business Faculty, Universitas Jenderal Achmad Yani. Work life balance as independent variable consist of time balance, involvement balance and satisfaction balance. And the job satisfaction as dependent variable measured by psychological factors, social factors, physical factors and financial factors. This research was descriptive and verificative method. Questionnaires were distributed to the lectures of the Economy and Business Faculty, Universitas Jenderal Achmad Yani. Saturated sampling technique was used in this research. And the techniques of data analysis uses Descriptive Statistics and Simple Linier Regression. The results showed that work life balance positively effect job satisfaction of lectures at Economy and Business Faculty, Universitas Jenderal Achmad Yani. Work life balance has an effect on the job satisfaction of lectures by 31.8%, while the rest was effected by other variables that is not examined in this research.